Cost and environmental analysis and optimization of a new and green three-level waste heat recovery-based cogeneration cycle: A comparative study - Nikafshan Rad, Hima; Ghasemi, Amir; Marefati, Mohammad (Heliyon, 2024)
Effective and maximum utilization of waste heat from industrial processes and fossil plants can improve thermodynamic performance and declined the environmental impacts of waste heat discharge to the atmosphere. Here, the multi-aspect assessment and optimization of a novel cogeneration power and cooling load cycle (CPCC) is developed. The considered cogeneration process is designed under a three-level waste heat recovery process consisting of an ORC (organic Rankine cycle) unit and an ejection-based refrigeration process. Thermodynamic performance, cost feasibility and environmental assessments of the suggested process have been comprehensively evaluated and discussed. A two-objective optimization is developed to minimize the total cost and maximize the exergy efficiency. Moreover, the comprehensive CPCC behavior is compared with a reference system (a single-level recovery/ORC process and a compression-based refrigeration process). The performance of the considered CPCC is also examined under various environmentally compatible refrigerants. The environmental analysis is based on two indicators (i.e., life cycle-climate performance and total equivalent-warming impacts). Due to the multi-level recovery of waste heat, the environmental impacts of emitting waste heat into the environment are significantly reduced. The outcomes revealed that the R1234/yf is considered as the most suitable refrigerant that can causes to optimum achievements for both systems. The exergetic performance is improved by about 10.3% compared to that reference system, while the exergy destruction and total annual cost of the CPCC, respectively, are reduced by approximately 7.4% and 21.6% compared to the reference cycle. It was also found that about 11,640 tons of carbon dioxide can be reduced by using the ejector in the refrigeration process.